Selective Effects of Manual Massage and Foam Rolling on Perceived Recovery and Performance: Current Knowledge and Future Directions Toward Robotic Massages - Kerautret, Yann; Di Rienzo, Franck; Eyssautier, Carole; Guillot, Aymeric (Frontiers in Physiology, 2020)
Manual massage (MM) and foam rolling (FR) are commonly used by athletes for warm-up, recovery, and well-being. MM requires the intervention of an experienced physiotherapist, while FR is a recent self-administered technique. While both techniques were largely studied in isolation, we first provide a deep integrative literature analysis to gather their respective benefits, and then conceptually consider the corresponding motor control strategies. During MM, the person remains passive, lying on the massage table, and receives unanticipated manual pressure by the physiotherapist, hence resulting in a retroactive mode of action control with an ongoing central integration of proprioceptive feedback. In contrast, while performing FR, the person directly exerts pressures through voluntary actions to manipulate the massaging tool, through a predominant proactive mode of action control, where operations of forward and inverse modeling do not require sensory feedback. While these opposite modes of action do not offer any compromise, we then discuss whether technological advances and collaborative robots might reconcile proactive and retroactive modes of action control, and offer new massage perspectives through a stochastic sensorimotor user experience. This transition faculty, from one mode of control to the other, might definitely represent an innovative conceptual approach in terms of human-machine interactions.